Online Public Access Catalog Implementation Determines Information Accessibility In Vocational Libraries: Implementasi Katalog Akses Publik Daring Menentukan Aksesibilitas Informasi Pada Perpustakaan Kejuruan - Salsabilla Febrianti Efendi; Isna Fitria Agustina; Sifak Duwi Kistanti; Vivie Ida Isna Nur Aini; Lusi Indri Fauziah; Dewi Ratna Sari; Mivtha Mauludia (Proceedings of The ICECRS, 2025)
General Background Educational institutions continuously modernize learning facilities to meet digital disruption challenges through integrated information systems. Specific Background Indonesian vocational schools actively adopt the Online Public Access Catalog to modernize library services and facilitate information retrieval. Knowledge Gap Despite widespread adoption, numerous users remain unfamiliar with digital catalogs, preferring manual searches due to confusing interfaces and a lack of skilled library personnel. Aims This study explores the implementation of an integrated library system using George C. Edwards III's policy theory at SMK Negeri 1 Sidoarjo. Results Qualitative descriptive analysis reveals that while the digital catalog facilitates student information searches, optimal operation is hindered by inadequate user comprehension and a severe shortage of staff possessing library science backgrounds. Furthermore, communication transmissions remain suboptimal, and resource limitations restrict system maintenance. Novelty This research comprehensively applies Edwards III's public policy framework to isolate specific bureaucratic and resource-based barriers in vocational library digitization. Implications Educational stakeholders must prioritize routine user training, secure adequate maintenance budgets, and upgrade personnel competencies to guarantee successful digital transitions. Highlights: Inadequate user comprehension causes students to rely on manual collection searches instead of the digital system. A shortage of personnel with specific library science backgrounds hinders optimal digital system operation. The implementation of the digital catalog successfully facilitates student information searches despite existing operational and bureaucratic barriers. Keywords: Integrated System, Policy Implementation, User Comprehension, Human Resources, Digital Transformation